CRISPR/Cas9-based genome editing of banana for disease resistance - Tripathi, L.; Ntui, V.O.; Tripathi, J.N. (Elsevier, 2020)
Banana production is severely constrained by many pathogens and pests, particularly where a number of them are co-existing. The use of disease-resistant banana varieties is one of the most effective ways to mitigate the negative impacts of pathogens on banana production. Recent advances in new breeding techniques have the potential to accelerate breeding of banana for disease resistance. The CRISPR/Cas9 based genome editing has emerged as the most powerful tool for crop improvement due to its capability of creating precise alterations in plant genome and trait stacking through multiplexing. Recently, the robust CRISPR/Cas9-based genome editing of banana has been established, which can be applied for developing disease-resistant varieties. This article presents a synopsis of recent advancements and perspectives on the application of genome editing for generating disease-resistant banana varieties. It also summarizes the current status of regulatory requirements for the release of genome-edited crop varieties among different countries.